Protecting Public Health Rights in Yazd Province: Prioritizing Challenges and Solutions - Saeed Hosseini; Vali Bahrevar; Zahra Naqibi Nodoushan; Seyed Masood Mousavi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: The right to health is one of the fundamental human rights, which includes access to healthcare services, suitable living conditions, and a healthy environment. In Iran, this right is clearly stated in the Constitution and key documents, and the government is responsible for providing these services to all individuals. In Yazd Province, a committee for the protection of people's rights in health has been established to identify the challenges and implementation problems in this area. This research has been conducted qualitatively and quantitatively to identify and prioritize issues related to individuals’ health rights in Yazd Province.